Improvement of bonding force between abrasive grains and matrix in Cu/diamond composite fabricated by centrifugal mixed-powder method - Hisashi SATO (The Japan Society of Mechanical Engineers, 2016)
As drilling process for carbon fiber reinforced plastic (CFRP), gyro-driving drilling machine has been proposed. Recently, Cu-based diamond grinding wheels for this drilling machine have been fabricated by using centrifugal mixed-powder method (CMPM). However, because diamond abrasive grains in this grinding wheel are dispersed into pure Cu matrix, drop out of the diamond grains occurs due to low wettability between Cu and diamond. In this study, improvement of bonding force between Cu matrix and diamond grains in Cu/diamond composite fabricated by the CMPM is investigated. As improvement method, Ti particles are added into mixed-powder used for the CMPM. This addition of Ti particles forms thin TiC layer at interface between the Cu matrix and the diamond grain. Thickness of the TiC layer increases as the amount of Ti particles in the mixed-powder increases. As the results, the bonding force between the Cu matrix and diamond grains is improved by the addition of Ti particles. The bonding force is increased as Ti concentration in the mixed-powder increases up to 2 mass%. When the Ti concentration exceeds 2 mass%, the bonding force is saturated. Also, the Cu/diamond composite containing Ti makes larger worn groove on counter disc used for wear test comparing with the composite without Ti. Therefore, the addition of Ti particles into the mixed-powder can be expected to enhance grinding ability of Cu-based diamond grinding wheel fabricated by the CMPM.